The Enemy on Display The Second World War in Eastern European Museums - Bogumił, Zuzanna (Berghahn Books, 2015)
Eastern European museums represent traumatic events of World War II, such as the Siege of Leningrad, the Warsaw Uprisings, and the Bombardment of Dresden, in ways that depict the enemy in particular ways. This image results from the interweaving of historical representations, cultural stereotypes and beliefs, political discourses, and the dynamics of exhibition narratives. This book presents a useful methodology for examining museum images and provides a critical analysis of the role historical museums play in the contemporary world. As the catastrophes of World War II still exert an enormous influence on the national identities of Russians, Poles, and Germans, museum exhibits can thus play an important role in this process
Description based on online resource; title from PDF title page (publisher's Web site, viewed 07. Nov 2022)
Keywords: Museum; Zweiter Weltkrieg; Sammlung; Ausstellung; Kollektives Gedächtnis; Musealisierung; ART / Museum Studies; Collective memory -- Europe, Eastern; Deutsche; Erinnerungskultur; Geschichtsbild; Geschichtspolitik; Identität; Memorialization -- Europe, Eastern; Museum exhibits -- Europe, Eastern; Osteuropa; Polen/Bevölkerung; Russen; World War, 1939-1945 -- Europe, Eastern; World War, 1939-1945 -- Influence; World War, 1939-1945 -- Museums -- Europe, Eastern